CHARACTERIZING Dalbergia cochinchinensis COMMUNITIES IN TAN PHU FOREST PROTECTION ZONE, DONG NAI - Van Viet, Nguyen; Hong Hai, Nguyen; Thi Thanh Thuy, Phan; Hung, Lee, Chun- (Journal of Forestry Science and Technology, 2020)
Dalbergia cochinchinensis Pierre is an endangered, precious, rare plant and also a priority native species to conserve in Vietnam. This paper shows the structural characteristics of D. cochinchinensis communities in natural forests in Tan Phu protection forest area, Dong Nai. 19 plots were set up on the poor forest, medium forest and rich forest types. The results showed that D. cochinchinensis distributed in poor forest, medium forest and rich forest types with density change by 74 trees/ha, 21 trees/ha, and 18 trees/ha, respectively. In overstory trees, there were 60 species in the medium forest which is higher 1.71 times and 1.25 times in comparison with the poor forest and rich forest. D. cochinchinensis only appeared in the species composition of the poor forest and the medium forest type with respective shares 9.1% and 5.0% of the important value index. All species richness, Shannon, Margalef, Fisher and Simpson indices of overstory trees were the lowest value in the poor forest type and the highest value in the medium and rich forest type. The distributions of the number of trees per DBH class of the three forest types were reverse J-shaped or decreased while the distributions of the number of trees per height class of all forest types were all left skewed and were well simulated by Weibull 2-parameter distribution functions. The medium forest has the highest number of regeneration species with 53 species, higher 1.20 times and 1.61 times compared with the poor forest (44 species) and the rich forest (33 species), respectively. The number of D. cochinchinensis seedlings regenerated in the poor forest was higher than that in the medium forest type with the composition species (N%) accounted for 10.6% (640 trees/ha) and 4.2% (440 trees/ha) of regeneration ratio, respectively; D. cochinchinensis has not recorded in the rich forest type.